The myth of the community fix: inequality and the politics of youth punishment - Cate, Sarah D. (Oxford University Press, 2023)
"The chapter also outlines the approach of the book, which provides a qualitative assessment of changes within the justice system and situates them within a broader policy and historical context. This perspective explores how youth are being treated, what is happening to those no longer sent to state-run prisons, and the complex political story behind how this reform model developed and garnered widespread support. These reforms contribute to a larger pattern of American social policy development toward devolution, privatization, and an emphasis on individual responsibility, rather than on eliminating economic and political inequalities"--